Carbothermal synthesis of nano-iron-carbon composites for arsenate removal from high-arsenic acid wastewater. Issue 2 (April 2022) - Kong, Yanli; Li, Mengxing; Zhou, Yangyang; Pan, Rui; Han, Zhao; Ma, Jiangya; Chen, Zhonglin; Shen, Jimin
Abstract: The current carbothermal method involves impregnation and reduction of ferric salt with the problems of low product activity and high cost, limiting the large-scale production and application of nano-zero-valent iron (nZVI). In this work, the nano-iron-carbon composites (CB-nZVI) were successfully synthesized at a high efficiency, low consumption and batch production process and showed a rapid and efficient As(V) removal from high-arsenic acid wastewater (pH<2 and As(V)> 5 g/L). More than 99.77% As(V) was removed by CB-nZVI under optimum reaction conditions of pH 1.7, initial As(V) concentration 5 g/L and nZVI dosage 11 g/L at 40 ℃ with approximately 11 mg/L As(V) still remained in the filtrate. A novel continuous two-stage treatment process was proposed with only 0.12 mg/L As(V) remained in the filtrate, which met the demands specified in Emission Standard of Pollutants for the Sulfuric Acid Industry issued by Ministry of Environmental Protection of China (GB26132–2010), and solid wastes were greatly reduced at the same time. The iron species distributed on the CB-nZVI core-shell structure possessed a high chemical reduction potential gradient driving force which resulted in the adsorbed As(V) would further be reduced to As(III) and As(0) and then diffusing across the thin oxide layer, leading to accumulating or immobilizing the arsenic at the CB-nZVI. Moreover, strongly acidic condition and Fe/C micro-electrolysis could accelerate the corrosion of CB-nZVI and generate iron oxides for As(V) adsorption. These results suggested that CB-nZVI has great potential for the disposal of strongly acidic wastewater with high concentration in the smelting industry. Graphical Abstract: ga1 Schematic of As(V) removal by CB-nZVI The unique features of the core-shell structure of CB-nZVI synthesized played a critical role for As(V) rapidly and high efficiency removal from the actual water that with high arsenic-containing strongly acidic industrial wastewater. Multiple mechanisms such as adsorption, precipitation, coprecipitation, complexation, especially the chemical reduction coexisted for As(V) removal by the CB-nZVI. The iron species distributed on the core-shell structure possessed a high driving force of chemical reduction potential gradient and its disorder and defective was favor for As(V) reduction, diffusion and the immobilization. The strongly acidic and Fe/C micro-electrolysis have synergic effects, which facilitated iron corrosion continuously generated, resulting in highly effective separation and encapsulation of As(V) by CB-nZVI. Highlights: An improved carbothermal method was presented to synthesis the nano-iron-carbon composites (CB-nZVI). The CB-nZVI synthesized showed a rapid and efficient As(V) removal from high-arsenic acid wastewater. A novel continuous two-stage treatment process was proposed. Multiple mechanisms especially the chemical reduction coexisted for As(V) removal.